Development of Fiber Optic Sensor-Based Weight-In-Motion System For Bridge Applications - Fatimah Nur Hidayah; Nugroho Tri Atmoko (Department of Physics, Sebelas Maret University, 2024)
Vehicles loaded with Over Dimension Overload (ODOL) cause damage to road infrastructure, traffic accidents, and endanger crossing transportation. ODOL vehicles also contribute to the death of people. This research focuses on characterizing the effect of moving loads on fiber optic light loss. Problem-solving approach through the optical fiber macrobending method. This research aims to be implemented in the WIM system concept. Macrobending comes from the weights contained in the body dump. The types of loading carried out are static and dynamic. Under dynamic loading, the speed variation is 0.1 m/s, 0.2m/s, and 0.3 m/s. The research results show that the greater the loading value, the greater the attenuation value of the optical fiber. This research applies to all three speed variations of the dummy dump truck, both front and rear wheels. Apart from that, the best sensitivity value is found at a speed variation of 0.1 m/s. The value is 2.029. This data can be used as a reference for the most recommended speed when a loaded vehicle passes through a fiber optic sensor-based WIM system.